(untitled) (Economics and region, 2025)
The article examines the conceptual foundations of forming Ukraine’s tourism image under the conditions of global transformations caused by globalization, digitalization, ecological challenges, geopolitical instability, and migration dynamics. The study substantiates the theoretical and methodological principles for constructing a positive tourism image of the state based on the integration of public diplomacy, regional identity, and the sociocultural potential of the nation. The research highlights the importance of a systemic and multi-level approach to image formation that combines institutional state policy, regional branding initiatives, and civil society participation. The author emphasizes the strategic role of communication tools and public diplomacy in shaping the perception of Ukraine in the global tourism market. Particular attention is paid to the analysis of national branding projects such as Ukraine Now and Brand Ukraine, as well as regional initiatives including Authentic Carpathians and Discover Dnipro, which strengthen territorial identity and cultural attractiveness. The study explores how global media narratives and international partnerships affect the country’s reputation and its positioning as a safe, authentic, and culturally diverse tourist destination. A structural model of tourism image formation is proposed, which reflects the interconnection between global factors, state institutional policies, regional identity, and sociocultural foundations. It is argued that a coherent image policy, supported by digital communication, cultural diplomacy, and tourism marketing, enhances the international recognition of Ukraine, contributes to its sustainable development, and fosters cross-cultural understanding. The findings demonstrate that a positive tourism image of Ukraine not only promotes economic benefits through tourism flows but also strengthens the state’s reputation capital, global competitiveness, and soft power potential. The results are of practical importance for governmental and municipal authorities, tourism and hospitality organizations, image-making professionals, and academic institutions involved in international relations, tourism studies, and cultural policy research.